Operationalising the Recovery College model with people living with dementia: a realist review - Handley, M; Wheeler, C; Duddy, C; Wong, G; Birt, L; Fox, C; Moniz-Cook, E; Hackmann, C; Teague, B; West, J (Routledge, 2024)
Objectives Post-diagnostic support is a significant factor in facilitating personal recovery following a diagnosis of dementia, but access is often inconsistent and insufficient. Recovery Colleges offer peer-led, co-produced courses that can support people to have meaningful lives and have been adapted for use in the context of dementia. A realist review was conducted to understand the application and sustainability of Recovery College dementia courses.